Woody species diversity, Foristic Composition and Structure of Däbrä libanos monastery forests, Central Ethiopia: Hingabu Hordofa Koricho (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2013)
Ethiopia is a country that has varying agro-ecological zones. This has given rise to a botanical treasure house containing 7,000 different flowering plants out of which 12% are probably endemic. This entire diverse flora is found in the natural forests which once covered 35% of the country’s total land area,2 but has now considerably shrunk. Different studies reveal that 3.1 million hectares of the total land of ýOromia, excluding desert forest and bamboo, is covered by forest, which constitutes 8.5% of the region’s total land and 75% of the country’s forest coverage. However, due attention has not been given to the protection and conservation of it.3 The Ethiopian Orthodox Tewahido parish churches give great value to the preservation of natural forests as indicated by the presence of dense and attractive forests that are conserved by monasteries and churches